Clinical progression, pathological characteristics, and radiological findings in children with diffuse leptomeningeal glioneuronal tumors: A systematic review - Jiang, Haoxiang; Qiu, Lu; Song, Juan; Xu, Dandan; Sun, Lei; Feng, Yinbo; Zhao, Jun; Qian, Jun; Yu, Zhiwei; Peng, Jin (Frontiers in Oncology, 2022)
Abstract Background: Diffuse leptomeningeal glioneuronal tumors are rare leptomeningeal neoplasms composed of oligodendrocyte-like cells characterized by neuronal differentiation and a lack of isocitrate dehydrogenase gene mutation. Purpose: We aimed to analyze the clinical progression, pathological characteristics, and radiological findings of diffuse leptomeningeal glioneuronal tumors in children, as well as the relevance of clinico-radiological data. Data Sources: We searched MEDLINE, PubMed, and Web of Science to identify case reports, original articles, and review articles discussing diffuse leptomeningeal glioneuronal tumors published between 2000 and 2021. Study Selection: The analysis included 145 pediatric patients from 43 previous studies. Data Analysis: Data regarding patient pathology, MRI manifestations, clinical symptoms, and progression were collected. The relationship between imaging classification and pathological findings was using chi-square tests. Overall survival was analyzed using Kaplan–Meier curves. Data Synthesis: Parenchymal tumors were mainly located in the intramedullary areas of the cervical and thoracic spine, and patients which such tumors were prone to 1p-deletion (χ2=4.77, p=0.03) and KIAA1549-BRAF fusion (χ2=12.17, p<0.001). The median survival time was 173 months, and the survival curve fell significantly before 72 months. Parenchymal tumor location was associated with overall survival (p=0.03), patients with KIAA 1549-BRAF (+) and treated with chemotherapy exhibited a better clinical course (p<0.001). Limitations: The analysis included case reports rather than consecutively treated patients due to the rarity of diffuse leptomeningeal glioneuronal tumors, which may have introduced a bias. Conclusions: Early integration of clinical, pathological, and radiological findings is necessary for appropriate management of this tumor, as this may enable early treatment and improve prognosis.